ANTXR1 deficiency promotes fibroblast senescence: implications for GAPO syndrome as a progeroid disorder - Przyklenk, Matthias; Karmacharya, Shreya; Bonasera, Debora; Pasanen-Zentz, Arthur-Lauri; Kmoch, Stanislav; Paulsson, Mats; Wagener, Raimund; Liccardi, Gianmaria; Schiavinato, Alvise (Scientific reports, 2024)
ANTXR1 is one of two cell surface receptors mediating the uptake of the anthrax toxin into cells. Despite substantial research on its role in anthrax poisoning and a proposed function as a collagen receptor, ANTXR1's physiological functions remain largely undefined. Pathogenic variants in ANTXR1 lead to the rare GAPO syndrome, named for its four primary features: Growth retardation, Alopecia, Pseudoanodontia, and Optic atrophy. The disease is also associated with a complex range of other phenotypes impacting the cardiovascular, skeletal, pulmonary and nervous systems. Aberrant accumulation of extracellular matrix components and fibrosis are considered to be crucial components in the pathogenesis of GAPO syndrome, contributing to the shortened life expectancy of affected individuals. Nonetheless, the specific mechanisms connecting ANTXR1 deficiency to the clinical manifestations of GAPO syndrome are largely unexplored. In this study, we present evidence that ANTXR1 deficiency initiates a senescent phenotype in human fibroblasts, correlating with defects in nuclear architecture and actin dynamics. We provide novel insights into ANTXR1's physiological functions and propose GAPO syndrome to be reconsidered as a progeroid disorder highlighting an unexpected role for an integrin-like extracellular matrix receptor in human aging.
Keywords: stárnutí buněk; fibroblasty; anodoncie; Actins; Progeria; Fibroblasts; Growth Disorders; Cellular Senescence; dědičné atrofie optického nervu; receptory buněčného povrchu; aktiny; poruchy růstu; mikrofilamentové proteiny; lidé; Humans; progerie; Receptors, Cell Surface; Alopecia; Microfilament Proteins; alopecie; Anodontia; Optic Atrophies, Hereditary